Genus Humidophila from caves in Serbia with an improved detailed description of rare H. brekkaensoides - Nikolić, Nataša; Popović, Slađana; Vidaković, Danijela; Subakov Simić, Gordana; Krizmanić, Jelena (Archives of Biological Sciences, 2020)
Paper description: Extreme habitats such as caves (entrances and spaces near artificial light) are inhabited by phototrophic microorganisms, including diatoms. Biofilm samples from 19 caves in Serbia were investigated to collect data about aerophilic diatoms. We analyzed the genus Humidophila, which includes species insufficiently explored and described. Seven species were found for the first time in Serbia, including a rare taxon H. brekkaensoides with different and additional features described than those presented in world literature. Since this genus was examined in cave habitats for the first time, upgraded knowledge about this genus diversity is presented in this study. Abstract: Phototrophic microorganisms can be found in biofilms at entrances to caves where they have access to sufficient sunlight, water and nutrients; however, they can also be found inside caves, where they are carried by animals and people, and can proliferate in the presence of artificial light. Although the genus Humidophila includes some well-known cosmopolitan species, further exploration of its rare, insufficiently investigated representatives in different geographical areas and unusual habitats is necessary. Caves remain unknown, little-explored habitats, and many species currently known to science were recorded for the first time. This study aimed to report species belonging to the genus Humidophila that were identified in 19 caves in Serbia. A total of ten species of this genus were recorded and some of them are documented for the first time in Serbia. The most abundant species were H. contenta (found in 16 caves), H. paracontenta, and H. aerophila (found in 13 caves), whereas H. pyrenaica was identified in only one cave. The rare species, H. brekkaensoides and H. vidalii, were also documented and described, but with different dimensions from those provided in current identification keys. https://doi.org/10.2298/ABS200228022N Received: February 28, 2020; Revised: April 17, 2020; Accepted: May 10, 2020; Published online: May 13, 2020 How to cite this article: Nikolić N, Popović S, Vidaković D, Subakov Simić G, Krizmanić J. Genus Humidophila from caves in Serbia with an improved detailed description of rare H. brekkaensoides. Arch Biol Sci. 2020;72(2):279-89.